A Ramesside Stela Fragment with Unusual Offerings (Cairo Agricultural Museum, No.4286) (Global Journal of Human-Social Science, 2023)
Publication of a Ramesside Stela fragment made of fine white limestone with figure and remains of text engraved with a sunk inscription figs 1-2 The Stela is kept in Cairo Agricultural Museum and according to the museum register the stela bears identification no 4286 The provenance of the stela is unknown